The Influence of Teacher Discipline on Students’ Learning Motivation in Elementary School Context: Evidence from GMIT Oesapa, Indonesia - Bani, Maria M.; Mbuik, Heryon Bernard; Nitte, Yulsy Marselina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher discipline plays a crucial role in shaping structured learning environments that influence students’ learning motivation. This study examines the effect of teacher discipline on students’ learning motivation in an elementary school context. A quantitative ex post facto design was employed involving 29 fifth-grade students selected through saturated sampling. Data were collected using validated Likert-scale questionnaires and analyzed using simple linear regression with SPSS version 25. The results indicate a positive and statistically significant relationship between teacher discipline and students’ learning motivation (p = 0.049). The regression coefficient (β = 0.523) suggests that higher teacher discipline is associated with increased learning motivation. The coefficient of determination (R² = 0.368) shows that teacher discipline explains 36.8% of the variance in students’ learning motivation. The findings confirm that teacher discipline functions as an external motivational determinant in elementary education settings. The study contributes to the literature by positioning teacher discipline as a behavioral construct that shapes motivational learning outcomes in faith-based elementary schools in Indonesia.